The Effects of Welding Parameters on Macro and Micro-Structure of Friction Stir Welded Aluminium - Ismail, A. (Institute of Physics Publishing, 2019)
Friction stir welding (FSW) is considered as state-of-the-art technology for joining aluminium alloys (AA). Several welding parameters with different rotational and travel speed combinations are used to produce good friction stir welded AA6063 pipe butt joint. The weld quality is then evaluated by optical microscope through observations of the macro and microstructure. The different welding parameters give finer grain structure on the weld nugget zone instead of irregular size of grain structure on the thermo-mechanically affected zone (TMAZ) and heat affected zone (HAZ). Thus, it would be useful for predicting mechanical performances (fracture) of FSW pipe butt joints. Â© Published under licence by IOP Publishing Ltd.